DAMPAK COVID-19 TERHADAP PEREKONOMIAN MASYARAKAT (STUDI KASUS PENDAPATAN USAHA KULINER DI TENGAH PANDEMI PADA KELURAHAN TANJUNG SARI KECAMATAN MEDAN SELAYANG KOTA MEDAN) - ARISMAN PARHUSIP; AMRIL . (LP2MTBM MAKARIOZ, 2021)
This study examines the impact of the COVID-19 on the income of the culinary business in the Tanjung Sari sub-district,Medan Selayang sub-district, Medan city. This study aims to determine the impact caused by the COVID-19 pandemic onthe economic situation in the community, especially in small and medium businesses, namely culinary businesses. The datacollection process was carried out by conducting interviews with several traders who sell culinary in Tanjung Sari village,namely along Jalan Setia Budi around it, totaling 15 Culinary Business. This research approach uses a qualitative descriptivemethod. The results of the study show that the impact of the Covid-19 pandemic is that the level of people's purchasingpower decreases due to decreased income so that the income of traders, especially culinary traders, is discussed in thisstudy.